ANALISIS SELEKSI TENAGA PENDIDIK DI YAYASAN BAITUL JANNAH BANDAR LAMPUNG - Yohanson, AK (Jurnal Manajemen Magister Darmajaya, 2018)
In improving the quality of education is very related to the problem of human resources, therefore the process of recruitment and selection of human resources (HR) is very important and can only be obtained through effective selection efforts that involve accurate and sustainable management functions. so that the qualifications in accordance with the field of work are obtained and the objectives of an educational institution are achieved. therefore, the HR selection process is one of the most important things in achieving the goals of an educational institution. This research used a qualitative method with a descriptive approach; Data collection through interviews as the main method and documentation as a supporting method in research, data analysis with reducing the data from interviews and documentation, then the data obtained is displayed, then conclusions are taken. The validity test of the data used is source triangulation. The data sources in this research are the Chairman of the Foundation, Head of the HR Division, Headmaster, Teacher, Secretary and office Staff. Based on the results of the research it can be concluded that; Selection conducted at the Baitul Jannah Foundation can be said good, because it is done in a systematic way, the selection consists of 2 (two) step, that is a preparation and implementation. Steps of preparation (including the activities of establish a selection team, preparing assessment instruments, preparation of place and time. And at the implementation steps (including the activities of administrative selection, beginning interviews, micro teaching, final interview and last decisions of result selection).However, it is necessary to improve the test in terms of measuring general and psychology knowledge which has only been explored through interviews, therefore written tests need to be carried out so that the results will become more valid and authentic.Keywords — Selection, Teachers